Incorporating patient perspectives in the science of uterus transplantation. (4th January 2022) - Farrell, Ruth M.; Falcone, Tommaso
Abstract : Linked article: This is a mini commentary on Wall et al., pp. 1095–1102 in this issue. To view this article visit https://doi.org/10.1111/1471-0528.17052